Our Experiences and Learnings in Diagnosing MODY from Non-Institutional-Based Diabetes Care Clinics - Arunkumar R. Pande; Santosh Chaubey; Dinesh Kumar; Kumar P. Chandra; Thenral Geetha; Akshita Sharma (Indian Journal of Endocrinology and Metabolism)
Introduction: Maturity-onset diabetes of the young (MODY) is a rare group of disorders characterised by impaired functions or development of pancreatic islets and monogenic diabetes at a young age. Diagnosing MODY can be rewarding for both clinicians and patients as it can change the management from generic to targeted therapy. Methods: This study reports the retrospective analysis of data collected from four clinics between March 2016 and February 2023 from Lucknow, a city in northern India. Fifty-three individuals are suspected to be affected by MODY based on ISPAD guidelines. Following a detailed clinical evaluation, they were referred for genetic diagnostic testing. Results: The cohort consists of 19 females and 34 males with a mean age of diagnosis of 25.3 years and a body mass index of 22.3 Kg/m2. Genetic testing detected variants in 13/53 (~24.5%) individuals. Five cases had significant pathogenic/likely pathogenic variants, HNF1A gene in two [(p.Phe268LeufsTer74) (p.Arg200Gln)], one each in HNF4A (Arg311His), PDX1(p.Ala228GlyfsTer33), and a case with suggestive digenic variants in HNF1A gene (p.Arg200Gln) and HNF1B [(p.Leu13Met)]. Variants of uncertain significance (VUSs) with inconclusive evidence of pathogenicity were reported in eight patients, and five were considered to be clinically significant as they are lean young onset, sulfonylurea-responsive, and presented with diabetes without acanthosis nigricans and with high pretest probability. These individuals harboured variants in HNF1A (p.Thr425_Thr429delinsPro), HNF1B (p.Ser19Phe), CEL (p.Val681ArgfsTer6), ABCC8 (p.Ile872Met), and KCNJ11 (p.Arg221Cys) genes. Conclusion: We found a diagnostic yield of around 10% of pathogenic or likely pathogenic variants in individuals who were suspected to have MODY. As it is a field that is still evolving, we might consider starting with oral agents under close supervision in those individuals who have VUS; there are some proportions of individuals who might not have classical sulfonylurea-responsive genetic variants, but they might respond to it.